Complex Visceral Coupling During Central Sleep Apnea in Cats - Limanskaya, Alexandra V.; Busygina, Irina I.; Levichkina, Ekaterina V.; Pigarev, Ivan N. (Frontiers in Neuroscience, 2020)
Central sleep apnea is a sudden arrest of breathing during sleep caused by the central commands to the thoracoabdominal muscles. It is a widespread phenomenon in both healthy and diseased people, as well as in some animals. However, there is an ongoing debate whether it can be considered as a pathological deviation of the respiratory function or an adaptive mechanism of an unclear function. We performed chronic recordings from six behaving cats over multiple sleep/wake cycles, which included electroencephalogram, ECG, eye movements, air flow, and thoracic respiratory muscle movements, and in four cats combined that with the registration of myoelectric activity of the stomach and the duodenum. In these experiments, we observed frequent central cessations of breathing (for 5–13 s) during sleep. Each of the sleep apnea episodes was accompanied by a stereotypical complex of somatic and visceral effects. The heart rate increased 3–5 s before the respiration arrest and strongly decreased during the absence of respiration. The myoelectric activity of the stomach and the duodenum also often demonstrated a strong suppression during the apnea episodes. The general composition of the visceral effects was stable during all periods of observation (up to 3 years in one cat). We hypothesize that the stereotypic coupling of activities in various visceral systems during episodes of central sleep apnea most likely reflects a complex adaptive behavior rather than an isolated respiratory pathology and discuss the probable function of this phenomenon.